PENERAPAN TERAPI UAP MINYAK KAYU PUTIH PADA ANAK DENGAN BRONKOPNEUMONIA DI RSUD KARDINAH TEGAL - Jatmiko, Heli; Yunida Triana, Noor (NHM PRESS, 2025)
Bronchopneumonia is an inflammatory disease of the respiratory organs that affects several lobes in the lungs. WHO data shows that bronchopneumonia mostly affects children under 5 years old and is the biggest cause of death in children. Bronchopneumonia will generally have typical symptoms such as shortness of breath and coughing. Children under the age of five cannot remove secretions independently so they will experience problems with ineffective airway clearance and children are at high risk of experiencing shortness of breath. Efforts to overcome shortness of breath in bronchopneumonia children can be overcome by using complementary therapies, one of which is eucalyptus oil steam therapy. Eucalyptus oil is produced from the leaves of the melaleuca plant with its largest content of eucalyptol (cineole). The properties of cineole produce mucolytic effects to thin phlegm, relieve breathing, and anti-inflammatory. This study aims to determine the effect of steam therapy with eucalyptus oil on respiratory frequency in patients with bronchopneumonia. This research is an analytical descriptive research with a case study approach. The subjects were children with bronchopneumonia who experienced shortness of breath. The study was conducted by providing steam therapy using warm water mixed with 2 drops of eucalyptus oil in a container and then inhaling the steam for 10-15 minutes, with 3x24 hours of intervention. Data collection was carried out by interview, observation and documentation study. The results showed a decrease in respiratory frequency in the subject from 26x/min to 21x/min. In conclusion, steam therapy with eucalyptus oil is effective in reducing the respiratory frequency of paediatric patients with bronchopneumonia.